THE FEDERAL CONSTITUTION, NATIONAL- ETHNIC MINORITY GROUPS AND THE CREATION OF STATES: THE POST–COLONIAL NIGERIAN EXPERIENCE - Emmanuel Obikwu (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2017)
Critics will retort that there are well over 400 ethno-linguistic groups in Nigeria and each of them cannot have their own state! This is acknowledged and is not an altogether unfounded claim. It, however, underestimates inter-communal and inter-ethnic relations which in Nigeria is generally cordial. Several states in the country are strictly speaking not entirely homogenous ethnically but are composed of several minority groups living together in harmony. Furthermore, there are criteria which ethnic groups agitating for states within Nigeria must meet. Political negotiations, rallies, campaigns and the like all play a part in the realization of the legitimate aspirations of ethnic minorities within a constitutional democracy. Undoubtedly, the operation of Federal Republican Constitution and the creation of states continues to attract constructive criticism. Thus, it has been argued against Nigeria’s Presidential Federalism that this type of republican constitutionalism continues to sustain and perpetuate the status of the predominant tribes more powerfully than would have occurred in a unitary system. Abstrak: Para kritikus akan membantah bahwa ada lebih dari 400 kelompok etnolinguistik di Nigeria, dan masing-masing kelompok tidak dapat memiliki negara sendiri! Klaim ini diakui dan bukan tidak berdasar sama sekali. Namun, klaim ini meremehkan hubungan antar komunal dan antar etnis yang umumnya terjadi di Nigeria. Beberapa negara bagian di Nigeria tidak sepenuhnya homogen secara etnis, melainkan terdiri dari beberapa kelompok minoritas yang hidup bersama secara harmonis. Selain itu, ada kriteria yang harus dipenuhi oleh kelompok etnis yang mengacaukan negara bagian di Nigeria. Negosiasi politik, aksi unjuk rasa, kampanye, dan sejenisnya berperan merealisasikan aspirasi yang sah dari etnis minoritas dalam demokrasi konstitusional. Tidak dapat dipungkiri bahwa operasi Konstitusi Republik Federal dan pembentukan negara bagian terus mengundang kritik yang konstruktif. Dengan demikian, bertentangan dengan Federalisme Presidensial Nigeria, jenis konstitusionalisme republikan ini akan lebih mempertahankan dan melestarikan status suku-suku dominan daripada sistem kesatuan. Kata kunci: Konstitusi Federal, Kelompok Etnis Minoritas, Paska kolonial